Feminist Trilogy in Lollywood: Exploring Female Transcendence In Blockbuster Pakistani Movies - Dr. Noshina Saleem , Dr. Hanan Ahamad Mian , Dr. Nasim Ishaq , Dr. Masroor Ahmed , Maria Sabir Rana (Migration Letters, 2024)
Over years, cinema became a great pillar in the economic growth, in shaping culture and traditional norms of a country. Traditional cinema presented women as docile beings existing to present male counterpart as heroes but it changed with the arrival of modern cinema. A big name in revival of cinema is Shoaib Mansoor who made movies focusing on women, their issues in society and presented female characters that transcended the barriers created by patriarchal system to hold women down for strengthening male dominancy in society. This study focuses on Pakistani movie trilogy, that is Khuda Ke Liye (2007), Bol (2011) and Verna (2017), depicting women as strong beings, capable of much more than what men think of them. It’s a qualitative study using critical discourse analysis (CDA). Results affirms that this movie trilogy makes contribution to Lollywood for women as it considers women to be its main audience and discusses issues faced by woman in a male dominant society. The females in these movies cross the patriarchal boundaries set by society to achieve their goals creating a way for women empowerment.